Factors that influence in the teaching the object pronouns and subject pronouns in the ninth year of basic education. - Nagua Cartuche, María Janeth (Machala : Universidad Técnica de Machala, 2015)
El principal objetivo de la presente investigación es determinar los factores que influyen para que el maestro no tiene éxito en los estudiantes de los nueve años de educación básica el uso correcto de los pronombres sujeto y objeto pronombres. pronombres sujeto o pronombres personales son los pronombres que funcionan como sujeto en una oración y pronombres de objeto se utiliza para sustituir los nombres que son el objeto directo o indirecto de una cláusula, por lo tanto, es muy importante que el maestro tiene un conocimiento claro sobre los temas que se enseñar, de manera que los estudiantes no tendrán problemas para aprender y tener éxito en la comprensión de la clase.
The main objective of the present investigation is to determine factors that influence so that the teacher does not succeed in the students of the ninth year of basic education the correct use of subject pronouns and object pronouns. Subject pronouns or personal pronouns are those pronouns that function as subject in a sentence and object pronouns are used to replace nouns that are the direct or indirect object of a clause, therefore it is very important that the teacher have clear knowledge about the topics that will teach, so that students will not have problems to learn and succeed in understanding the class.
Keywords: FACTOR; TEACHING; OBJECT PRONOUN; SUBJECT PRONOUN